The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.2134/jeq2018.05.0196
|View full text |Cite
|
Sign up to set email alerts
|

Diatom Assemblage Changes in Agricultural Alluvial Plain Streams and Application for Nutrient Management

Abstract: In large, alluvial floodplains dominated by agriculture, small streams have the potential to experience nutrient enrichment affecting algal assemblage structure and metabolism. Nutrient enrichment is largely driven by application of nutrients and altered hydrologic regimes. To inform stressor–response‐based nutrient reduction goals for agricultural alluvial plain streams, diatom assemblages were sampled from 25 streams located within the Mississippi Alluvial Plain (MAP) with various land management practices a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…Recently, homogenization of diatom communities has also been observed in response to hydrological alterations and urbanization in Mediterranean rivers which also led to significant species loss at both local and regional scales (Falasco et al, 2021a) and a reduced role of diatoms in the total benthic chlorophyll-a (Piano et al, 2016). Moreover, the present study confirmed the high trophic value of some species, mainly collected in the R-C macrotype, such as N. gregaria (Hicks and Taylor, 2019;Hausmann et al, 2016;Szczepocka et al, 2016), Nitzschia palea (Licursi et al, 2016;Szczepocka et al, 2016;Yang et al, 2015), Gomphonema parvulum (Lu et al, 2020;Szczepocka et al, 2016) and C. euglypta (Trábert et al, 2020). S. nigri was confirmed as one of the most tolerant diatom species (see Hausmann et al, 2016 as Eolimna minima;Yang et al, 2015).…”
Section: Diatom Communities and Water Quality In The Two Macrotypessupporting
confidence: 83%
“…Recently, homogenization of diatom communities has also been observed in response to hydrological alterations and urbanization in Mediterranean rivers which also led to significant species loss at both local and regional scales (Falasco et al, 2021a) and a reduced role of diatoms in the total benthic chlorophyll-a (Piano et al, 2016). Moreover, the present study confirmed the high trophic value of some species, mainly collected in the R-C macrotype, such as N. gregaria (Hicks and Taylor, 2019;Hausmann et al, 2016;Szczepocka et al, 2016), Nitzschia palea (Licursi et al, 2016;Szczepocka et al, 2016;Yang et al, 2015), Gomphonema parvulum (Lu et al, 2020;Szczepocka et al, 2016) and C. euglypta (Trábert et al, 2020). S. nigri was confirmed as one of the most tolerant diatom species (see Hausmann et al, 2016 as Eolimna minima;Yang et al, 2015).…”
Section: Diatom Communities and Water Quality In The Two Macrotypessupporting
confidence: 83%
“…Understanding how diatom community assembly is linked to environmental factors is a vital key to improving agricultural eutrophic rivers ecosystem management [2]. In Lalin River Basin, the main factors emanating from agricultural activities that impacted the aquatic organisms were organic and persistent organic pollutants [1,20].…”
Section: Discussionmentioning
confidence: 99%
“…During the past decades, however, agricultural practices have significantly increased, causing visible effects on rivers (overuse of pesticides or fertilizer, etc. ), but their impacts have been very difficult to assess [2,3]. Ice-covered periods of rivers can play an essential role in nutrient cycling and biodegradation in rivers of the temperate zone [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, many diatom species are indicators of TP concentrations >100 µg/L (Potapova and Charles 2007), suggesting that additional changes in taxa and assemblage structure in high nutrient systems could be expected. Though less common, some studies have reported changes in diatom species and assemblages at higher TP (up to 156 µg TP/ L) and TN (up to 1,100 µg TN/L) concentrations (Smith and Tran 2010, Chambers et al 2012, Lavoie et al 2014, Hausmann et al 2016, Taylor et al 2018, Hicks and Taylor 2019.…”
Section: Diatom Responses To Nutrientsmentioning
confidence: 99%